ALL POCUS TB study: abdominal and lung point-of-care ultrasound for tuberculosis - Denkinger, Claudia M. (Universität, 2024)
Study Protocol and Statistical Analysis Plan for ALL POCUS TB Study --- ALL POCUS TB is a prospective, cross-sectional multicentre cohort study in which the accuracy and the diagnostic yield of Tuberculosis-focused point-of-care ultrasound (POCUS) and image interpretation with artificial intelligence (AI) will be assessed in inpatients and outpatients with presumed TB disease in German and Indian sites. Dedicated POCUS protocols for the diagnosis of HIV-associated extra-pulmonary tuberculosis (EPTB) in high incidence settings have been proposed, but reliable accuracy data for both patients with and without HIV are thus far limited. Another arising ultrasound field with great potential is lung ultrasound (LUS) for the diagnosis and the assessment of disease extent for pulmonary TB. Our study ultrasound protocol will cover both abdominal and thoracic locations in both HIV(+) and HIV(-) patients. In addition, we will follow up patients with confirmed TB under anti-mycobacterial therapy to document the natural evolution of TB-associated sonographic findings and assess their value for monitoring of therapy success. With this study we want to fill this gap and to guide implementation efforts by better characterizing the sensitivity and specificity of sonographic findings for TB diagnosis against a comprehensive reference standard. POCUS has the potential to increase TB case finding and avoid over-diagnosis. A study on the accuracy of point-of-care ultrasound for the diagnosis of thoracic and abdominal TB. We investigate the accuracy of both single tuberculosis associated findings as well as composite findings such as combinations of pathological changes. We are enrolling patients with presumed TB regardless of HIV-status and will perform subgroup analysis for patients with/without TB and patients with/without diabetes mellitus as possible risk factors. The aim is the description of possible combinations for a point-of-care protocol, which can be used as a non-sputum based triage test for TB. In addition, we evaluate patients longitudinally with ultrasound to determine the value for therapy monitoring for pulmonary and extrapulmonary findings.
Gefördert durch: German Center for Infection Research (Deutsches Zentrum für Infektionsforschung): Grant TTU 02.911
Gesehen am 11.07.2024
Keywords: Forschungsdaten; Datenbank